Work Migrants: Some Positive Implications for the Enhancement of the Self - Keini, Noga Levine; Helper, Amit (Advances in Social Sciences Research Journal, 2022)
The self is the core of the personality and the more it becomes well established the more it will generate a sense of heightened self-esteem. In this article we will suggest that the self is a complex and multi-faceted organization. This is particularly relevant to the sphere and experience of work migrants in their work migration. Their experience is such that they often find themselves in strange and unfamiliar circumstances that are frequently lonely and anxiety-inducing. In this article we will focus on and explore the multi-faceted self, based on the findings of in-depth interviews of 28 work migrants who came to Israel from India, Nepal and the Philippines. We will examine the varied states of self that evolved from the complex experiences of work migration. This conceptualization is drawn from object relations theories and those of relational theorists regarding the self.